Liver cyst with biliary communication treated with endoscopic ultrasound-guided drainage: A case report. Issue 11 (18th March 2022) - Shionoya, Kento; Koizumi, Kazuya; Masuda, Sakue; Suno, Yuma; Kawachi, Jun; Kimura, Karen; Makazu, Makomo; Kubota, Jun; Nishino, Takashi; Sumida, Chihiro; Tasaki, Junichi; Ichita, Chikamasa; et al.
Abstract: Rationale: Simple liver cysts are common, and usually benign and asymptomatic, requiring little to no treatment. Liver cysts with biliary communication, however, are rare and require effective treatment to avoid recurrence. Patient concerns: A 70-year-old woman with breast cancer visited our hospital for treatment. Physical examination revealed abdominal distension and bilateral lower leg edema. Diagnosis: Abdominal contrast-enhanced computed tomography revealed a giant liver cyst, inducing inferior vena cava compression that was causing her edema. Interventions: Percutaneous transhepatic cyst drainage was performed. Since the bilirubin level in the drained fluid was high, the patient was diagnosed with a liver cyst with biliary communication. After the procedure, her symptoms improved and the cyst decreased in size. However, the drainage volume did not decrease after approximately 2 weeks. Sclerotherapy with minocycline was ineffective. Thus, endoscopic retrograde cholangiopancreatography was performed, and an endoscopic nasobiliary drainage tube was inserted. The percutaneous drainage tube was clamped, and the cyst showed increase in size. Therefore, endoscopic ultrasound-guided cyst drainage, which is less invasive than surgery, was performed. Outcomes: The cyst tended to decrease in size even after the percutaneous drainage tube had been removed. At 3years follow-up, the cyst has almost disappeared. Lessons: Endoscopic ultrasound-guided drainage can treat liver cyst with biliary communication.